John Palmer Usher correspondence - Usher, John Palmer, 1816-1889.
Transcript of a letter from Usher to his wife, Margaret Patterson Usher, describing the death of Abraham Lincoln. Includes details of Lincoln's last cabinet meeting and Usher's theories about the assasination
Typewritten transcript.
Lawyer and U.S. secretary of the interior.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Assassination; Lincoln, Abraham, -- 1809-1865 -- Death and burial; United States -- Politics and government -- 1861-1865.; Usher, Margaret Patterson -- Correspondence; Cabinet officers; Lawyers